The Design and Making Prototype of pressing equipment for Banana with Capacities 90 kg/hour - Tri Atmodjo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2012)
Banana plants in Indonesia can grow well both high and lowland, from the temperate wet and dry climate. In addition to the consumption of fresh banana in Indonesia a few cultivars are also widely used as industrial raw material chips, “sale pisang” and banana flour. Many craftsmen who developed food banana in the form of sale due to ease in the manufacturing process, in addition to food enthusiasts sale high enough banana. Making banana sale in the domestic industrial scale is still mostly done by hand which is only capable of producing 20 kg / hour in the form of processed banana fruit in banana sale. So many craftsmen maker banana sale household scale industries can not buy banana in large numbers. In the manufacture of sale of banana is done manually are still many shortcomings, which measure the thickness of the sale of banana produced uneven. In general, pressing machine banana sale is a tool that changes the shape of banana from thick to thin size. By utilizing the roll rotation that drives the conveyor belt top and conveyor belt bottom of the moving direction. In this study is designed pressing sale banana toot driven electric motor with power 2 hp 1 phase with a speed of 1400 rpm. With a shaft diameter of 25 mm, the size of the pegs 10x22 mm whit a depth of 5 mm. Gear is used in this reduction type where a large number of gear as much as 115 teeth, gear motor driver as much as 9 teeth and roll gear driver as much as 15 teeth. Bearings used in the manufacture of this pressing banana sale tool is bearing 6305 ZZ C3 P6 type. Resulting of test manufacturing pressing banana sale tool conducted showed that the pressing machine capable flattens banana sale with an average size of 10.16 cm in length banana sale, with 3.3 cm and 0.36 cm thick with a capacity of 90 Kg/hour or in day (7 hour) machine capable of pressing flattens banana sale much as 630 Kg/day.Keywords: Banana plants, pressing, machine design